Sister chromatid exchange in healthcare personnel exposed to antineoplastic drugs in a Lima hospital complex - Cruz-Bueza, Fredy (2022)
Cytogenetic biomonitoring techniques allow early detection of exposure to genotoxic agents and the sister chromatid exchange assay (SCE) that was applied aimed to evaluate these effects in peripheral blood lymphocytes of health personnel exposed to antineoplastic drugs in a Hospital Complex of Lima. The exposed group was subdivided according to the proximity to the oncological preparations in: direct, intermediate and low contact, in addition there was a control group. The information was analyzed in the statistical program IBM SPSS 25.0. Statistically significant differences were found in the frequencies of exchanges in the groups of health personnel with direct and intermediate exposure compared to the control group (P<0.05), the comparative analysis between personnel with leave and the control group did not show significant differences. These findings allow evidence of a higher risk of genotoxicity for health personnel exposed to antineoplastic drugs.